Investigation of Tribological and Strength Properties of ABS/CF Fibrous Composites Formed in Fused Deposition Modeling - Prusinowski, A.; Kaczyński, R. (Journal of friction and wear, 2020)
The subject of this study are tribological and strength properties of composites with matrix material in the form of thermoplastic plastics and a reinforcing material in the form of carbon fibers used in 3D printing technology—Fused Deposition Modeling. Simulation results of matrix material flow in the nozzle are presented. An analysis of the matrix material mixing process in the designed system was carried out and we developed our own conclusions. The article presents the method of forming this type of composite using a printhead at the stage of fabrication of an element. The possibility of modifying the geometrical distribution of reinforcing fibers in an element of the composite being tested by modifying the height of the layer of the applied material has been demonstrated. The relationship between the distance of subsequent carbon fiber bundles and the assumed height of the layer of applied material has been presented. Test results of abrasive wear and tensile strength of obtained materials with different percentages of reinforcing fibers are presented.